Flow generation at daily level using the GR4j Method and gridded climate information in the Huayabamba river basin (LACCEI, 2024)
Given the small number of hydrometric records, this research aims to generate daily and monthly flows for the Huayabamba river basin up to its confluence with the Huallaga river, for the period between the years 1980-2020, this in order to This information can be used in the future for the elaboration of hydrological and hydraulic projects, which can mitigate flooding in the towns established in the lower part of the basin. For this reason, to achieve this purpose, the ERA5 temperature and precipitation grid information and the GR4j runoff precipitation method were used.